2013
DOI: 10.4103/1305-7456.120683
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different root canal medicaments on the elimination of Enterococcus faecalis ex vivo

Abstract: Objective:The aim of this study was to evaluate the antimicrobial effect of chlorhexidine gel (CHX-G) 2%, chlorhexidine powder (CHX-P) 1%, povidone-iodine (PVP-I), polyhexanide and camphorated-and-mentholated chlorophenol (ChKM) ex vivo.Materials and Methods:For every medicament group 10 root segments (15 mm long) of extracted human teeth were prepared to ISO-size 45 and sterilized (n = 50). The root segments were then inoculated with Enterococcus faecalis and aerobically incubated at 37°C. After 1 week, ten r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 40 publications
1
24
0
4
Order By: Relevance
“…Several earlier studies have reported co-prevalence of Streptococcus , Rothia , Granulicatella , Gemella , Actinomyces , Selenomonas , Haemophilus and Veillonella in caries samples,[ 1 2 7 8 9 10 ] very similar to the observation made in the present study. But, what makes our study significant is that the co-prevalence of the bacteria was observed in the saliva samples of caries samples, in contrary to plaque or dentinal caries samples reported in other studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several earlier studies have reported co-prevalence of Streptococcus , Rothia , Granulicatella , Gemella , Actinomyces , Selenomonas , Haemophilus and Veillonella in caries samples,[ 1 2 7 8 9 10 ] very similar to the observation made in the present study. But, what makes our study significant is that the co-prevalence of the bacteria was observed in the saliva samples of caries samples, in contrary to plaque or dentinal caries samples reported in other studies.…”
Section: Discussionsupporting
confidence: 92%
“…Some of the most commonly reported bacteria include Lactobacillus , Granulicatella , Gemella , Haemophilus , Veillonella , Actinomyces , Rothia , Selenomonas , Atopobium , Neisseria , Eikenella , Fusobacterium , Leptotrichia , and Enterococcus . [ 1 2 7 8 9 10 ] Several studies have indicated co-existence of above bacteria in various combinations, though the detection depended on the source of sample saliva, mature plaque or dentinal caries from primary, secondary or mixed dentition age groups. [ 11 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…as calcium hydroxide (CH). [3,4] Interestingly, this resistance to withstand the alkaline stress induced by CH is also shared with Candida albicans; another resistant pathogen in teeth with periradicular lesions with the prevalence of 6%-18%. [5,6] Both bacteria and fungi express a proton pump in their plasma membrane for energy metabolism and maintenance of constant cytoplasmic pH [7,8] that enables E. faecalis and C. albicans to maintain the homeostasis of the cytoplasm and survive the high alkaline pH of CH.…”
Section: Comparative Evaluation Of Antimicrobial Efficacy Of Triple Amentioning
confidence: 99%
“…However, ChKM and Cresophene are reported to reduce the viability of fibroblast cells. 7,8 Therefore, it suggested to find other environmentally friendly potential drugs, such as a herbal medicine, as an alternative for root canal sterilization with minimal side effects.…”
Section: Introductionmentioning
confidence: 99%